Research on physiological plan system of real-time acquisition and analysis of athletes physiological data in badminton training - Sun, Y. (BioTechnology: An Indian Journal, 2014)
Along with the rapid promotion of badminton skills under a new trend, competition rules, and requirements for the athletes are also increased. This study mainly studies the real-time acquisition and analysis of athletes physiological data in badminton training, to make valid training plan based on the actual situation of athletes, thus to set solid foundation for their further development. As badminton is a flexible activity, and requires coordination of various parts of the body to play their best, it can not only exercise the body, but also enhance the character. But in the study, there are many problems in badminton training to solve. To settle these problems, the Physiological Plan system is designed composing four levels, namely hardware, algorithm, interfaces, and data processing. These four levels are closely related. After a series of operation, the processed result will be presented to the coaches, which is the key of this study. The research focuses on studying Physiological Plan system for real-time capture and analysis of physiological data during the training, finding a fundamental solution to the current problems in the badminton training, so as to create conditions for coaches know more accurately about the state of badminton athletes in training and competitions. Staring from the development of Physiological Plan system, this study aims to research on the system working on athletes real-time acquisition and analysis of physiological data in the badminton training, in order to provide powerful theoretical support for the majority of researchers.